Multiplication of Raja bulu Banana (Musa paradisiaca L. AAB GROUP) on Several Benzyl Aminopurine (BAP) Concentration by Using In Vitro Method - Hertasning Yatim (Universitas Sumatera Utara, 2016)
The aim of this research was to study the effects of growth regulators BAP concentration on the number of leaves, shoots, and roots by using in vitro method. The research was conducted at the Tissue Culture Laboratory, Department of Agriculture, Banggai District in August - October 2015, This study used a Randomized Complete Design with one factor and six level of treatments i.e, BAP (M1 = 0.1 ppm; M2 = 1.0 ppm; M3 = 0.2 ppm; M4 = 2.0 ppm; M5 = 0.3 ppm; M6 = 3.0 ppm). The results showed that BAP at various concentrations was significantly influenced on the number of leaves at 4-10 weeks after planting, and have no significant effect on the number of shoots and roots.